The plot to save the planet: how visionary entrepreneurs and corporate titans are creating real solutions to global warming - Dumaine, Brian (New York : Crown Business, 2008)
Environmental aspects.
Includes bibliographical references and index.
Keywords: Industrial management -- Environmental aspects; Renewable energy resources -- Economic aspects